DEVELOPMENT AND PERFORMANCE OF GLYCOL-BASED DEEP EUTECTIC SOLVENT IN EXTRACTIVE DESULFURIZATION SYSTEM - MAJID, MOHD. FARIDZUAN (2020)
The release of sulfur dioxide from fuel combustion is now becoming an environmental and human health concern. To encounter this, hydrodesulfurization (HDS) is implemented to produce low sulfur fuel oil, however it requires harsh operation conditions and hard to remove steric sulfur such as dibenzothiophene. Extractive desulfurization (EDS) is one of the alternative processes that have been explored to remove sulfur via extraction. Many researchers used organic solvent and ionic liquid as extractant in EDS, however it is unfeasible for industrial application due to the pricy solvent and high toxicity.